2017
DOI: 10.1016/j.beth.2017.06.003
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis of Compassion-Based Interventions: Current State of Knowledge and Future Directions

Abstract: Future directions are provided for compassion research, including the need for improved methodological rigor, larger scale RCTs, increased specificity on the targets of compassion, and examination of compassion across the lifespan. Although further research is warranted, the current state of evidence highlights the potential benefits of compassion-based interventions on a range of outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

26
433
3
8

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 607 publications
(470 citation statements)
references
References 63 publications
26
433
3
8
Order By: Relevance
“…Overall, the changes experienced by the high‐adherence group presented medium effect sizes, which indicates that participation in the training programme enhanced mindfulness skills and self‐compassionate attitudes, and promoted positive outcomes, that is, subjective well‐being. The results are consistent with the findings from a meta‐analysis by Kirby et al (), who found that compassion‐based interventions generally produced medium effect‐size changes in outcome variables such as self‐compassion, mindfulness and well‐being, among others. Neff and Germer () found changes of a large and moderate magnitude for self‐compassion and mindfulness, respectively, following participation in the MSC training, which was assessed through a randomised controlled trial design.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Overall, the changes experienced by the high‐adherence group presented medium effect sizes, which indicates that participation in the training programme enhanced mindfulness skills and self‐compassionate attitudes, and promoted positive outcomes, that is, subjective well‐being. The results are consistent with the findings from a meta‐analysis by Kirby et al (), who found that compassion‐based interventions generally produced medium effect‐size changes in outcome variables such as self‐compassion, mindfulness and well‐being, among others. Neff and Germer () found changes of a large and moderate magnitude for self‐compassion and mindfulness, respectively, following participation in the MSC training, which was assessed through a randomised controlled trial design.…”
Section: Discussionsupporting
confidence: 90%
“…Mindfulness is a fundamental component of most trainings that aim to cultivate compassionate attitudes towards other people and the self. Various interventions focused on training compassion and/or self‐compassion through mindfulness‐based practices have been shown to produce changes in a wide range of symptoms and well‐being‐related outcomes (Kirby, ; Kirby, Tellegen, & Steindl, ). For instance, the Mindful Self‐Compassion (MSC) programme is intended for use in clinical and non‐clinical settings (Neff & Germer, ).…”
Section: Introductionmentioning
confidence: 99%
“…Self-compassion skills may assist cancer survivors by facilitating self-care in the face of adversity. A recent meta-analysis of RCTs using compassion-based interventions with mental health populations shows medium effects on anxiety (d = .49) and depression (d = .64; Kirby, Tellegen, & Steindl, 2017). A recent meta-analysis of RCTs using compassion-based interventions with mental health populations shows medium effects on anxiety (d = .49) and depression (d = .64; Kirby, Tellegen, & Steindl, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Although many psychotherapies predominantly target barriers to functioning, positive psychology approaches focus on building resources to support functioning. A range of compassion‐based therapies exist, which share the principle that compassion is a powerful method of regulating threat‐based emotions such as shame and self‐criticism (Kirby, Tellegen, & Steindl, ). Compassion has been defined as “a sensitivity to suffering in self and others, with a commitment to try to alleviate and prevent it” (Gilbert, , p.19).…”
Section: Introductionmentioning
confidence: 99%